PENGARUH SKILL REPRESENTASI HANDS ON ACTIVITY TERHADAP PENGUASAAN KONSEP GETARAN DAN GELOMBANG SISWA SMP - Ervina Septiani; Nengah Maharta; Abdurrahman - (Jurnal Pembelajaran Fisika, 2013)
This research has a purpose to (1) identify the influence of hands on activity representation skill towards the Vibration and Wave concept mastery among junior high school students and (2) the improvement of Vibration and Wave concept mastery among junior high school students by using hands on activity representation skill. Based on the research, data gathered in hands on activity representation skill and concept mastery and after that they have been analyzed by using SPSS 17.0 Program. The analysis results showed that the data distributed normally and linearly. The research hypotheses testing used correlation method, simple regression linear and paired t-test sample. The results of the research showed that :(1) there was a positively and linearly significant influence towards concept mastery amounted to 45,70% which was a determination coefficient value. It was gained from correlation coefficient value amounted to 0,676 in strong category and regressive equation where coefficient values a and B were significant coefficients. (2)There is an significantly average improvement in junior high school students’ concept mastery caused by the influence of hands on activity representation skill amounted to 36,37 with N-gain average concept mastery amounted to 0,64 in moderate category.Keywords : hands on activity representation skill and mastery of concept